A solution of coupled nonlinear differential equations arising in a rotating micropolar nanofluid flow system by Hermite wavelet technique - Kumbinarasaiah, S.; Raghunatha, K. R.; Rezazadeh, Mohammadreza; İnç, Mustafa (Springer, 2022)
In this article, the two-dimensional micropolar rotating nanofluid between two parallel plates under Hall's influence can be solved using the Hermite wavelet technique (HWT). The nanofluid flow between two parallel plates is taken under the influence of the Hall current. The flow of micropolar nanofluid has been assumed in a steady state. We obtain a coupled, highly nonlinear ordinary differential equations (ODEs) from the fundamental governing equations via appropriate similarity variables. The behavior of velocity, temperature, concentration, and micro rotation are computationally discussed concerning the various governing parameters. Our outcome illustrates that the HWT is immensely capable and accessible for finding solutions to this type of coupled nonlinear ODEs. The results are in outstanding agreement for coupled nonlinear ODEs in engineering applications.
Keywords: Nonlinear differential equations; The operational matrix of integration; Collocation method; Hermite wavelets